The persistence of performance of South African unit trusts - C. Firer; J. P. Beale; M. D. Edwards; J. N. Hendrie; D. C. Scheppening (South African Journal of Business Management, 2001)
This study examines persistence of performance in South African general equity and fixed income unit trusts over the period January 1989 to December 1999. The formation and holding periods studied ranged from one quarter to two-years. Significant persistence was found for most combinations of formation and holding periods for risk-adjusted equity unit trusts. It is suggested that choosing equity unit trust winners from the previous two-years and holding them for the next two-years may be the best long-term strategy to adopt. The fixed income unit trusts showed far less significant persistence than the equity unit trusts with loser-loser persistence predominating.
Keywords: 650